Music to move the masses : protest music of the 1980s as a facilitator for social change in South Africa - Mohr, Claudia (College of Music, 2015)
In this research project I will endeavour to show how protest music, specifically during the 1980s, became an instrument with which musicians and the public themselves strived to counteract the social perceptions generated under apartheid. I will show how the protest music movement of the 1980s was able to contribute to the greater cultural revolution of the era by providing a medium through which South Africans could formulate a new collective identity. In this regard it is important to note that the term ‘protest music,’ as applied throughout this research project, refers to any music that in its form, aesthetic nature or context can be seen to raise objections against the status quo.